Pengaruh Gaya Kepemimpinan, Lingkungan Kerja Terhadap Kinerja Karyawan dengan Motivasi Sebagai Variabel Intervening: Studi Kasus pada PT Perkebunan Nusantara IV Distrik 1 Unit Bukit Lima Kab.Simalungun - Khesara Niros Gulo; Calen; Henry D. Pardede (MES Management Journal, 2025)
Every employee needs a leader who can create a great work atmosphere and increase motivation because motivated employees perform better and meet company objectives more rapidly. This study aims to determine the positive and noteworthy impacts of leadership style and motivation on staff performance at PTPN IV Unit Bukit Lima, Simalungun Regency. This study uses a quantitative approach. The number of samples for the random sampling technique was calculated using the Slovin formula of 222 employees. Primary data collected through the distribution of surveys and secondary data with documentation were among the data sources. This study makes use of path analysis using SPSS 26.0 software. The results show that leadership style, work environment, and motivation all have a positive and significant impact on employee performance at PTPN IV Bukit Lima Unit, Simalungun Regency. At a significance threshold of 0.05, the t-values for leadership style (3,381), work environment (5,666), and motivation (7,380) are all slightly higher than the t-table (1,97190). Additionally, simultaneous analysis shows that the Fvalue (595,616) is greater than the Ftabel (3,88), suggesting that all four variables combine to have a large and positive impact on employee performance. Based on the coefficient of determination test, the variables Leadership Style, Work Environment, and Motivation have a positive and significant impact on Employee Performance, making up 86.3% of the total, as indicated by the Adjusted R Square value of 0.863. Other factors not covered in this study have an impact on the remaining 13.7%.